Cross compatibility in five species of Capsicum - AHMAD, K P SUNIL, RASHEED (Journal of Spices and Aromatic Crops, 1998)
Evaluation of 160 accessions of Capsicum which included five species and their inter specific hybrids at Chalode (Kerala, India) indicated that C. chinense (110.3 ASTA unit colour and 186.2 g per plant yield) and the hybrid C. annuum x C. chinense (58.6 ASTA unit colour and 190.3 g per plant yield) were the most promising and can be used as sources of colour for improving the present day chilli cultivars.